Association Between VEGF-460C/T Gene Polymorphism and Risk of Diabetic Retinopathy in Type 2 Diabetes Mellitus: A Meta-Analysis - Cheng, Bo; Wu, Aimin; Zhou, Xuewei (Hormone and Metabolic Research, 2024)
The aim of the study was to investigate the relationship between VEGF-460C/T polymorphism and susceptibility to diabetic retinopathy (DR) in type 2 diabetes mellitus (T2DM) by meta-analysis. A comprehensive search was conducted across six databases until September 2023 to identify studies examining the association between VEGF-460C/T polymorphism and susceptibility to DR. Data process was performed by Stata 15.0 software. Eight studies were included, involving 1463 patients with DR. In the overall analysis, the difference was statistically significant only in the homozygous model (CC vs. TT: OR=1.86, p=0.048). A subgroup analysis of 6 papers with genotype frequency satisfying HWE in the control group indicated significant differences among the allele (C vs. T: OR=1.34, p=0.037), recessive (CC vs. CT+TT: OR=1.96, p=0.022) and homozygous (CC vs. TT: OR=2.28, p=0.015) models. However, in the dominant and heterozygous models, the difference was not statistically significant. The sensitivity of the HWE-based subgroup analysis showed that the conclusions in other gene models except the heterozygote model were not robust. This meta-analysis indicated that VEGF-460C/T gene polymorphism is associated with susceptibility to DR in T2DM. Allele C and genotype CC at the VEGF-460C/T locus are associated with an increased risk of DR in T2DM. However, considering that the results are not robust, more trials involving more rigorous design are needed to verify the findings of this review in the future.
Keywords: VEGF; type 2 diabetes mellitus; diabetic retinopathy; meta-analysis